2012
DOI: 10.1258/la.2012.012101
|View full text |Cite
|
Sign up to set email alerts
|

Response to Roustan et al. ‘Evaluating methods of mouse euthanasia on the oocyte quality: cervical dislocation versus isoflurane inhalation’: animal welfare concerns regarding the aversiveness of isoflurane and its inability to cause rapid death

Abstract: Response to Roustan et al. 'Evaluating methods of mouse euthanasia on the oocyte quality: cervical dislocation versus isoflurane inhalation': animal welfare concerns regarding the aversiveness of isoflurane and its inability to cause rapid death

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…All data were analyzed using SPSS software ver. 19.0 (SPSS, Inc., Chicago, IL, USA). Statistical analyses were performed using one-way analysis of variance followed by Tukey's multiple comparison post hoc tests and P<0.05 was considered to indicate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All data were analyzed using SPSS software ver. 19.0 (SPSS, Inc., Chicago, IL, USA). Statistical analyses were performed using one-way analysis of variance followed by Tukey's multiple comparison post hoc tests and P<0.05 was considered to indicate a statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…All surgeries and euthanasia were performed under intravenous injection of sodium pentobarbital anesthesia (35 mg/kg, Sigma-Aldrich; Merck KGaA, Darmstadt, Germany). All mice were sacrificed using isoflurane (0.5 ml) euthanasia as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of published aversion studies available at the time (2006), the previous Newcastle meeting recommended that inhalant anaesthetics be used to render animals unconscious before switching to CO 2 . (Because of their wide safety margins, it is time consuming to kill animals with isoflurane [ 18 ] or halothane, so a secondary method is sometimes preferred for the sake of efficiency and safety). However, subsequent aversion studies have indicated that this may not necessarily be a refinement if animals have previously been exposed to inhalant anaesthetics (see below).…”
Section: Summary Of the Meetingmentioning
confidence: 99%
“…Automated carbon dioxide euthanasia systems have been validated and are commercially available (McIntyre et al, 2007). Cervical dislocation and decapitation of mice and rats less than 200 g can be rapid and humane if carried out by experienced operators, who were preferably trained on anesthetized animals, and as approved by the IACUC (Carbone et al, 2012b;Cartner et al, 2007;Golledge, 2012;Roustan et al, 2012;Leary et al, 2013). Guinea pigs may struggle excessively when exposed to carbon dioxide.…”
Section: H Euthanasiamentioning
confidence: 99%